Strategi Pengembangan Usaha Peternakan Sapi Potong di Kabupaten Pesisir Selatan - A Suresti; R Wati (Universitas Andalas, 2012)
The main objectives of this research were identifying internal and external factors in developing beefcattle and giving to determined strategies for the developing beefcattle implemented in Pesisir Selatan. A survey was conducted in 6 sub distric in Pesisir Selatan and the sampling technique used was purposive sampling. The data were analized using Internal Factor Evaluation (IFE), External factor Evaluation (EFE) and SWOT. The result showed that strategy that could be implemented in developing beefcattle was optimalization land function, increasing the beefcattle population, integrated farming areas, increasing agriculture production,giving better servicer on financial institutional for society optimalization.